Safety assessment of Bacillus subtilis CU1 for use as a probiotic in humans - Lefevre, Marie; Racedo, Silvia M.; Denayrolles, Muriel; Ripert, Gabrielle; Desfougères, Thomas; Lobach, Alexandra R.; Simon, Ryan; Pélerin, Fanny; Jüsten, Peter; Urdaci, Maria C. (Regulatory toxicology and pharmacology, 2017)
Bacillus subtilis CU1 is a recently described probiotic strain with beneficial effects on immune health in elderly subjects. The following work describes a series of studies supporting the safety of the strain for use as an ingredient in food and supplement preparations. Using a combination of 16S rDNA and gyrB nucleotide analyses, the species was identified as a member of the Bacillus subtilis complex (B. subtilis subsp. spizizenii). Further characterization of the organism at the strain level was achieved using random amplified polymorphic DNA polymerase chain reaction (RAPD PCR) and pulsed field gel electrophoresis (PFGE) analyses. B. subtilis CU1 did not demonstrate antibiotic resistance greater than existing regulatory cutoffs against clinically important antibiotics, did not induce hemolysis or produce surfactant factors, and was absent of toxigenic activity in vitro. Use of B. subtilis CU1 as a probiotic has recently been evaluated in a 16-week randomized, double-blind, placebo-controlled, parallel-arm study, in which 2 × 109 spores per day of B. subtilis CU1 were administered for a total 40 days to healthy elderly subjects (4 consumption periods of 10 days separated by 18-day washouts). This work describes safety related endpoints not previously reported. B. subtilis CU1 was safe and well-tolerated in the clinical subjects without undesirable physiological effects on markers of liver and kidney function, complete blood counts, hemodynamic parameters, and vital signs. •A safety assessment of the probiotic Bacillus subtilis CU1 was conducted.•Genomic analyses identified the species as a member of the B. subtilis complex.•Antibiotic resistance was not observed at levels exceeding regulatory cut-offs.•B. subtilis CU1 was absent of toxigenic activity in vitro.•B. subtilis CU1 was safely consumed (2 × 109 spores/day) by all clinical subjects.